Trends and biases in research efforts for primate conservation: threatened species are not in the spotlight - Flávia de Figueiredo Machado; Barbbara Silva Rocha; Daniel Brito; Levi Carina Terribile (Perspectives in Ecology and Conservation, 2023)
The order Primates is a diverse group with worrisome conservation status, in which 67% of the species are threatened, and 85% have declining populations. Although the studies in primate conservation have increased over the past two decades, there is a lack of knowledge about the trends and biases in these conservation research efforts. We reviewed the primate conservation literature to identify the trends in allocating research efforts across species, themes, and countries. We also investigated whether the studies are biased by primate richness, species body mass, range size, locomotion type, diel activity, threat status, time since species description, and phylogenetic relatedness. We found that the highest number of studies was about habitat fragmentation. Madagascar, Indonesia, and Brazil concentrated most of the studies. Pan troglodytes was the most studied species. The conservation research efforts are skewed towards primate-rich countries, earlier-described and large species that use arboreal and terrestrial substrates, and that are phylogenetically related. Therefore, research in primate conservation seems more motivated by specific primate attributes rather than aspects of species vulnerability and their main threats. The elucidation of these trends and biases may help identify knowledge gaps and new research opportunities, contributing to optimizing future conservation research efforts in primate conservation.